2019
DOI: 10.1038/s41433-019-0363-9
|View full text |Cite
|
Sign up to set email alerts
|

Small aperture IC-8 intraocular lens in cataract patients: achieving extended depth of focus through small aperture optics

Abstract: Background To investigate visual outcomes following cataract surgery in patients who were implanted monocularly with an extended range of focus IC-8 IOL. Methods A multicentre, non-randomised, retrospective case series of 126 consecutive patients implanted with the IC-8 IOL. Data were collected and pooled from six centres across Australia. Uncorrected distance visual acuity (UDVA), uncorrected intermediate visual acuity (UIVA) at 80 cm and uncorrected near visual acuity (UNVA) at 40 cm were measured in eyes im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 22 publications
1
42
0
4
Order By: Relevance
“…Previous studies assessing the clinical performance of the IC-8 IOL were also in accordance with our results. 13,17,18 Dick et al 19 found monocular uncorrected UDVA (4 m), UIVA (67 cm), and UNVA (40 cm) values of 0.06 ± 0.15, 0.08 ± 0.12, and 0.18 ± 0.14 logMAR, respectively (105 patients, 6-month follow-up). When combined with an aspheric monofocal IOL, the binocular distance-corrected defocus curve revealed a visual acuity of 0.20 logMAR or better ranging from +1.00 to -2.00 D.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies assessing the clinical performance of the IC-8 IOL were also in accordance with our results. 13,17,18 Dick et al 19 found monocular uncorrected UDVA (4 m), UIVA (67 cm), and UNVA (40 cm) values of 0.06 ± 0.15, 0.08 ± 0.12, and 0.18 ± 0.14 logMAR, respectively (105 patients, 6-month follow-up). When combined with an aspheric monofocal IOL, the binocular distance-corrected defocus curve revealed a visual acuity of 0.20 logMAR or better ranging from +1.00 to -2.00 D.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative, non-diffractive, option for extending the depth of focus of an IOL is using a small aperture, such as is incorporated into the IC-8 IOL (Acufocus, Inc., Irvine, CA). 10 This provides a similar effect to “stopping down” a camera. The IC-8 IOL achieves the objective of an extended depth of focus, but at the expense of limiting the light entering the eye.…”
Section: Introductionmentioning
confidence: 96%
“…CA, USA) IOL einen Astigma-tismus von bis zu 1,5 dpt kompensieren kann[6]. Shajari et al zeigten, dass diese IOL einen hohen Sicherheitsindex und eine hohe Zufriedenheitsrate hat und bei irregulärem Hornhautastigmatismus zu einer besseren Sehqualität führen kann…”
unclassified